Transport and logistics in the Baltic Sea Region by 2030 : a foresight analysis for the HAZARD Project - Friman, Eeli (My University, 2019)
The aim of this thesis was to map the outlooks of transport and logistics in the Baltic Sea Region by the year 2030. The study was carried out as an assignment for the Interreg Baltic Sea Region Program’s HAZARD project. It was a follow up study to previous research by Ojala et al. (2013) and the graduate thesis by Leino (2014). The data was gathered with the Delphi-method by surveying a multinational expert panel consisting of 96 participants from the Baltic Sea Region. The survey included 52 questions, which were subdivided into 10 themes. Several factors anticipated to affect the region's competitiveness by 2030 were identified, of which the most important were the following: growing importance of environmental aspects, significant technological advances, increasing taxation and regulation, increasing prevalence of cyber threats, and the shortage of skilled blue-collar labor. Differences to the findings of the preceding Delphi-study study were minor. The largest change was in the question regarding the tightening border controls between EU countries and countries outside the Union. The border controlling was anticipated to intensify further and more clearly than in the previous study. The research responded to the findings by presenting the following seven policy recommendations for decision-makers: 1. Logistic aspects should be researched more thoroughly when making decisions, 2. Equipment and infrastructure should be prepared for tightening environmental regulation, 3. Tax and regulatory changes affecting the logistics sector need to be prepared for by taking into account the possible decreasing profitability, 4. Technological changes must be prepared for in order to enable the effective adoption of relevant innovations, 5. The upcoming lack of skilled workforce should be prepared for by investing in relevant education, 6. Cyber security needs to be increased in all parts of the supply chains, and 7. Possible alternative trade relations should be considered to prepare for the anticipated tightened border crossing between Russia and other Baltic Sea Region countries.
Keywords: Baltic Sea Region, Futures Studies, Transport, Logistics, PESTE, Delphi